(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the note-taking strategy (CORNELL) on systematic thinking among second-grade female students in government daytime secondary and intermediate schools. Al-Fadhila School was intentionally chosen to be its student sample for the research affiliated with the First Karkh Directorate for the academic year (2024-2025). Then one of the two sections was randomly chosen to represent the experimental group that studies according to the note-taking strategy (CORNELL) and the other the control group that studies according to the usual method. The equivalence of the two research groups was verified by a set of variables, which were represented by chronological age in months, previous achievement in chemistry, Raven intelligence test, previous information test), and it was concluded that the two groups were equivalent. As for the research tool, a scale of systematic thinking skills was built, which is represented by four main areas divided into thirty-seven paragraphs. After applying the scale, it was found that there was a statistically significant difference at the level (0.05) between the average scores of the experimental group students who studied according to the strategy and the average scores of the control group students who studied According to the usual method in favor of the experimental group, and in light of that, a set of recommendations and conclusions were developed.